2021
DOI: 10.1186/s13613-021-00914-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury prevalence, progression and long-term outcomes in critically ill patients with COVID-19: a cohort study

Abstract: Background There are limited data on acute kidney injury (AKI) progression and long-term outcomes in critically ill patients with coronavirus disease-19 (COVID-19). We aimed to describe the prevalence and risk factors for development of AKI, its subsequent clinical course and AKI progression, as well as renal recovery or dialysis dependence and survival in this group of patients. Methods This was a retrospective observational study in an expanded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
67
5
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 56 publications
(64 reference statements)
14
67
5
12
Order By: Relevance
“…In concordance, this was also reported by a UK study. 35 Although decreased mortality with remdesivir was not found, it decreased the incidence of AKI. 36 …”
Section: Discussionmentioning
confidence: 95%
“…In concordance, this was also reported by a UK study. 35 Although decreased mortality with remdesivir was not found, it decreased the incidence of AKI. 36 …”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the same analysis suggested an association between steroid use and kidney recovery, though it did not reach statistical significance, and in a separate recent study, steroid use was associated with reduced risk for AKI progression. 19 The observed association of steroid use with better kidney outcomes should be more systematically explored in subsequent larger clinical/epidemiologic investigations. Tocilizumab and remdesivir, which are also both now used more widely than during the study period, were not significantly associated with either kidney or mortality outcomes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to prior studies of AKI-KRT among critically ill patients without COVID-19, this study and other studies of patients with COVID-19 have found higher rates of in-hospital mortality and of dialysis dependence at hospital discharge. 1 , 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 These differences in outcomes may reflect the profound multiorgan failure associated with COVID-19 during the initial spring 2020 surge. The higher rate of kidney non-recovery may also be due to direct infection of the kidneys by the SARS-CoV-2 virus, though this remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…La IRA en pacientes hospitalizados con COVID-19 también aumenta el riesgo de desenlaces clínicos negativos [17] . Finalmente, la ERC puede desarrollarse en los meses posteriores al alta en los sobrevivientes a un IRA durante su hospitalización [18,19] . Entonces, el IRA o ERC causan un mayor riesgo de tener desenlaces clínicos negativos en comparación con los pacientes con función renal normal [20][21][22] .…”
Section: Introductionunclassified